Improving carbon monoxide tolerance of Cupriavidus necator H16 through adaptive laboratory evolution - Wickham-Smith, Charles; Malys, Naglis; Winzer, Klaus (Frontiers in Bioengineering and Biotechnology, 2023)
Background: The toxic gas carbon monoxide (CO) is abundantly present in synthesis gas (syngas) and certain industrial waste gases that can serve as feedstocks for the biological production of industrially significant chemicals and fuels. For efficient bacterial growth to occur, and to increase productivity and titres, a high resistance to the gas is required. The aerobic bacterium Cupriavidus necator H16 can grow on CO2 + H2, although it cannot utilise CO as a source of carbon and energy. This study aimed to increase its CO resistance through adaptive laboratory evolution. Results: To increase the tolerance of C. necator to CO, the organism was continually subcultured in the presence of CO both heterotrophically and autotrophically. Ten individual cultures were evolved heterotrophically with fructose in this manner and eventually displayed a clear growth advantage over the wild type strain. Next-generation sequencing revealed several mutations, including a single point mutation upstream of a cytochrome bd ubiquinol oxidase operon (cydA2B2), which was present in all evolved isolates. When a subset of these mutations was engineered into the parental H16 strain, only the cydA2B2 upstream mutation enabled faster growth in the presence of CO. Expression analysis, mutation, overexpression and complementation suggested that cydA2B2 transcription is upregulated in the evolved isolates, resulting in increased CO tolerance under heterotrophic but not autotrophic conditions. However, through subculturing on a syngas-like mixture with increasing CO concentrations, C. necator could also be evolved to tolerate high CO concentrations under autotrophic conditions. A mutation in the gene for the soluble [NiFe]-hydrogenase subunit hoxH was identified in the evolved isolates. When the resulting amino acid change was engineered into the parental strain, autotrophic CO resistance was conferred. A strain constitutively expressing cydA2B2 and the mutated hoxH gene exhibited high CO tolerance under both heterotrophic and autotrophic conditions. Conclusions: C. necator was evolved to tolerate high concentrations of CO, a phenomenon which was dependent on the terminal respiratory cytochrome bd ubiquinol oxidase when grown heterotrophically and the soluble [NiFe]-hydrogenase when grown autotrophically. A strain exhibiting high tolerance under both conditions was created and presents a promising chassis for syngas-based bioproduction processes.